2013 Ieee Sensors 2013
DOI: 10.1109/icsens.2013.6688330
|View full text |Cite
|
Sign up to set email alerts
|

Large animal detection and continuous traffic monitoring on highways

Abstract: There is an increasing interest worldwide in animal detection systems to reduce animal-vehicle collisions. Traditional approaches include building animal crossings, introducing real or virtual fencing, video surveillance and break-the-beam systems. Unlike these approaches, the system described here Large Animal Warning and Detection System (LAWDS) employs a 360˚-scanning radar to monitor a stretch of highway. This provides year-round continuous highway monitoring, even in harsh weather conditions. Innovative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A review of research into collisions that involved an animal found that the indicators used to trigger the warning messages of conventional RADS systems [12–17] were limited to the presence/absence of an animal within a detection area. As safety indicators are usually designed to analyse vehicle‐to‐vehicle collisions [20] rather than animal‐vehicle collisions, additional indicators were required.…”
Section: Conceptual Framework For An Ng Radsmentioning
confidence: 99%
“…A review of research into collisions that involved an animal found that the indicators used to trigger the warning messages of conventional RADS systems [12–17] were limited to the presence/absence of an animal within a detection area. As safety indicators are usually designed to analyse vehicle‐to‐vehicle collisions [20] rather than animal‐vehicle collisions, additional indicators were required.…”
Section: Conceptual Framework For An Ng Radsmentioning
confidence: 99%
“…In [20] Large Animal Warning and Detection System has been analyzed. This system was designed to detect large animals such as moose and dear.…”
Section: Lawdsmentioning
confidence: 99%
“…A variety of systems apart from cameras have been used for detecting animals. A Large Animal Warning Detection System (LAWDS) making use of a 360 degree radar was proposed by Mukherjee et al [5].…”
Section: Literature Reviewmentioning
confidence: 99%